2019
DOI: 10.3390/molecules24152695
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Containing MOFs as Seeds for the Preparation of Highly Active Fe/Al-SBA-15 Catalysts in the N-Alkylation of Aniline

Abstract: We have successfully incorporated iron species into mesoporous aluminosilicates (AlSBA15) using a simple mechanochemical milling method. The catalysts were characterized by nitrogen physisorption, inductively coupled plasma mass spectrometry (ICP-MS), pyridine (PY) and 2,6-dimethylpyridine (DMPY) pulse chromatography titration, powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX). The catalysts were tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…2). Mhadmhan et al 40 successfully incorporated iron species into an Al-SBA-15 material through the use of MOFs as metal seeds (MIL-53(Fe), MIL-88(Fe), and MIL-101(Fe)) to create stable and super-active Fe-containing catalysts for N -alkylation of aniline with benzyl alcohol. 40…”
Section: Fe-based Mof Structures Synthesized Via Different Routesmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Mhadmhan et al 40 successfully incorporated iron species into an Al-SBA-15 material through the use of MOFs as metal seeds (MIL-53(Fe), MIL-88(Fe), and MIL-101(Fe)) to create stable and super-active Fe-containing catalysts for N -alkylation of aniline with benzyl alcohol. 40…”
Section: Fe-based Mof Structures Synthesized Via Different Routesmentioning
confidence: 99%
“…Table 1 shows a comparison, in terms of properties, between materials obtained using conventional methods and those obtained using nonconventional approaches. [36][37][38][39][40][41][42]…”
Section: Fe-based Mof Structures Synthesized Via Different Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…A new method for the N‐alkylation of amines was put forth by Luque et al [ 29 ] Here, the catalyst was prepared by the introduction of Fe species into mesoporous aluminosilicates (Al‐SBA‐15) by mechanochemical milling method. It was then utilized for the conversion of aniline to imine (Scheme 3).…”
Section: Classificationmentioning
confidence: 99%
“…The 53MOF/Al-SBA-15 gave the best catalytic activity which indicated that the use of MOF as seeds was more effective than the use of FeCl 3 . Moreover, the 53MOF/Al-SBA-15 could reuse due to its stability of mechanochemically synthesized catalyst [83].…”
Section: Introductionmentioning
confidence: 99%